Comparative effect of auxin analogues on induction of polyhaploids in triticale and triticale wheat hybrids through wheat maize system - PRATAP, ADITYA; CHAUDHARY, HARINDER K (The Indian Journal of Agricultural Sciences, 2012)
The study was designed to evaluate two auxins, 2,4-D and picloram for their effectiveness for induction of polyhaploids in triticale and triticale × wheat crosses and to standardize their optimum dose. Ten F1 and parental genotypes pollinated with maize were subjected to in vivo auxin treatment at three concentrations (100, 250 and 400 mg/l) by injecting at the tiller base of the crossed spikes so as to fill the hollow of their uppermost internode. Both auxins restulted in formation of embryo-carrying seeds, though the performance differed significantly for the three parameters of haploid induction at different concentrations. The highest seed formation, embryo formation, and regeneration frequencies in 2,4-D were recorded at 250, 400 and 250 mg/ l concentration, respectively, whereas, 400, 400 and 250 mg/ l concentration of picloram, respectively, were best for above traits. All the genotypes led to regeneration of haploid plants at 250 mg/l of both the auxins. On the basis of the three haploid induction parameters and overall success rates, the 250 mg/l concentration of both auxins was optimum.